The Influence of Cyberculture on Lifestyle: A Case of New Media Users (Prithvi Academic Journal, 2023)
Computers and the Internet have brought significant changes in our daily activities. They bring people together throughout the world, influencing the lifestyle of people, and creating a new culture of sharing information. This culture is known as cyberculture. The objective of this study is to identify the impact of using computers and the Internet on people’s everyday life. Innovation in technology and new media has transformed the world into the digital age equipped with new tools and skills. The use of the internet has made us the first generation of artificial intelligence (AI) overcoming the limitation of time and distance. This study explores the changes brought about by information technologies on the lifestyle of the people of Pokhara Metropolis and the challenges they have faced. In this study, a quantitative research design has been adopted, using a descriptive-analytical method for the analysis of data collected from 52 respondents. The overall results indicated that participants have mixed views about influences as they have faced both opportunities and challenges in their lives while using media on daily basis. This study helps us understand the role of cyberculture in the process of fostering a sense of change in everyday life. It further helps the government to formulate digital policies and implement them among people.